Effect of the time interval between melanoma diagnosis and sentinel node biopsy on the size of metastatic tumour deposits in node-positive patients. (May 2022) - El Sharouni, Mary-Ann; Scolyer, Richard A.; van Gils, Carla H.; Ch'ng, Sydney; Nieweg, Omgo E.; Pennington, Thomas E.; Saw, Robyn PM.; Shannon, Kerwin; Spillane, Andrew; Stretch, Jonathan; Witkamp, Arjen J.; Sigurdsson, Vigfús; et al.
Abstract: Introduction: This study sought to assess whether the interval between diagnostic excision-biopsy of a primary melanoma and definitive wide excision with sentinel node biopsy (SNB) influenced the size of SN metastatic deposits, which might have implications for management and prognosis. Methods: Data were collected for (i) a Dutch population-based cohort of patients treated between 2004 and 2014 who underwent SNB within 100 days of complete excision of their primary melanoma and who were SN-positive with known SN metastasis diameter (n = 1027) and (ii) a cohort from a large Australian melanoma treatment centre (n = 541) who presented in the same time period. The effects of SNB timing on the size of SN metastatic deposits were analysed. Results: Dutch patients whose SNB was performed in the second or third months after diagnosis had significantly larger SN metastasis diameters than patients who had their SNB in the first month (median increases of 17% (95%CI -14, 60%, p = 0.211) and 71% (95%CI 15, 119%, p = 0.004), respectively). No significant difference in tumour diameter for early and late SNB was found in the Australian cohort. Conclusions: SN metastasis diameter became progressively greater with SN biopsy in the second and third months after primary melanoma diagnosis in the larger, population-based patient cohort. An increase in metastasis diameter was not observed in the smaller, institutional cohort, possibly due to detection of larger SN metastases by routine pre-operative ultrasound, with fine-needle biopsy confirmation. These patients did not proceed to SNB and were therefore not included in the study. Highlights: The interval between melanoma diagnosis and sentinel node (SN) biopsy varies greatly. This study examined the association between that time interval and SN tumour size. An effect on SN tumour size was found in only the larger of two patient cohorts. The effect of delayed SN biopsy on metastasis size requires further study.